Pengembangan Museum Jamu Jago Sebagai Sarana Wisata Kreatif (Pendekatan Pada Konsep Arsitektur Vernakular) - Maulina, Syirli; , Ir. Alpha Febela Pr, MT (2017)
Museum Jamu Jago is located in Setiabudi street No17, Srondol Semarang This museum is a museum MURI (Indonesian Record Museum), and PT. Jamu Jago. The existence of this museum is rarely visited by visitors as a destination for recreation, lack of facilities and other support to make this museum rarely glimpsed as a recreational destination because it seemed boring, The purpose of this research is to develop a museum Jamu Jago with supporting facilities complete with educational tourism, recreation areas and centers herbal medicine research. The emphasis that is Vernacular Architecture. The method is performed in the search for such data is by observation, study of literature, and interviews.